The philosophical and allegorical prose in the works of A. de Saint-Exupery: specific features - Jilevich, Olga F. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to the identification of specific features of the philosophical and allegorical prose, as one of the most relevant phenomenon in French literature of the XX century. The article reveals the peculiarities of the functioning of the allegory in the narrative of A. de Saint-Exupery’s philosophical and allegorical prose as an artistic-aesthetic means of the text and a constructive factor in the organization of the prose. Author's strategies are presented in the disclosure of the artistic concept of the world and man, in solving moral and ethical, philosophical and ontological problems.
Keywords: French literature; philosophical and allegorical novel; Antoine de Saint-Exupery; allegory; philosophical system; worldview